Environmental Status of Jenin District - Waleed Sa'eed Hussin Saqr (My University, 2005)
Environment is considered one of the important sides in human life, especially in the modern age, man started to have an interest in the environment in which he lives. The research discussed the environmental status in Jenin District which is considered one of Palestine Districts which is distinguished by its many assembles, this district is also distinguished by being agricultural in the first place. The research discussed the situation in this district from the human, and the natural sides such as location, history, the climate, geology and soil, agricultural situation, waters and their resources, education, transportation, economy and demographic situation. The research treats the problem of the lack of environmental enlightenment of the inhabitants, and it highlights the importance of environment to human beings, and the manner to maintain and keep it, and it also highlights the most sources of pollution in the district, and the manner to minimize this problem and to enlighten the in habitants of the danger of these pollutants and their effects on human health and environment. The research aims at studying the environmental situation in the district, and it aims at knowing the sources of pollution and their effects on the district, in addition to showing the degree of pollution in the district, and studying the inhabitants wrong behavior towards environment and their effect on causing pollution, and enlightening them . The researcher used the method of the generate theoretical frame through recognizing the history and geography of the district . And the method of getting information related to the study such as statistics, data personal interviews, personate observations, field study, photos and analysis of the existed situation . The results of the research showed that the economical, social and demographical features have a great effect in increasing the size of pollution. And that the morphology of Jenin district plays a role in the nature of land use distribution.And the quantity of solid waste increases in the dry season more than the humidity season . The results also showed that the waste differs from a place to an other according to location.And that the house solid waste occupyes the first place of waste And that the climate circumstances in creasing pollution in winter. And the unsuitability of waste places regarding inhabitant’s areas. And finally the results showed that the district is a victim of pollution in all its kinds.

تعتبر البيئة من الأركان المهمة في حياة الإنسان وبالذات في العصر الحديث، وقد أخذ الإنسان يهتم بالبيئة التي يعيش فيها، وقد تناولت الدراسة الحديث عن الوضع البيئي في محافظة جنين التي تعتبر إحدى محافظات فلسطين التي تمتاز بكثرة تجمعاته، وتمتاز هذه المحافظة بأنها زراعية بالدرجة الأولى عن باقي محافظات الضفة الغربية. وقد تم الحديث عن وضع هذه المحافظة من الناحية البشرية والطبيعية مثل الموقع وتاريخ المحافظة ومناخها وجيولوجيتها والتربة والواقع الزراعي والمياه ومصادرها والمواصلات والتعليم والاقتصاد والوضع السكاني. وتقوم الدراسة على معالجة مشكلة عدم وجود وعي بيئي لدى السكان الذي يكاد يكون معدوماً لدى غالبية السكان وتوعيتهم وإبراز أهمية البيئة للإنسان وكيفية المحافظة عليها وإبراز أهم مصادر التلوث في المحافظة وكيفية الحد من هذه المشكلة وتوعية السكان لخطر هذه الملوثات وأثرها على صحة الإنسان وبيئته. وتهدف الدراسة إلى دراسة الواقع البيئي في المحافظة والتعرف على مصادر التلوث وأثارها في المحافظة وإظهار درجة التلوث في المحافظة، ودراسة سلوك السكان الخاطئ تجاه البيئة وأثرهم في أحداث التلوث وتوعيتهم. وتم استخدام طريقة الإطار العام النظري من خلال التعرف على تاريخ المحافظة وجغرافيتها. واستخدمت في الدراسة طريقة الحصول على المعلومات المتعلقة بالدراسة من إحصاءات وبيانات ومقابلات شخصية والملاحظات شخصية والدراسة الميدانية والصدر والتحليل للواقع الموجود. ومن اهم النتائج التي تم التوصل إليها ان للخصائص الاقتصادية والاجتماعية والسكانية والديمغرافية أثر كبير في حجم التلوث وتلعب مورفولوجية محافظة جنين في طبيعة توزع استخدامات الأرض، وتزداد كمية النفايات الصلبة في فترة الجفاف عنها في فترة الرطوبة. وتختلف النفايات من مكان إلى أخر تبعاً لاختلاف الموقع، وتحتل النفايات الصلبة المنزلية المرتبة الأولى في النفايات، وكذلك اسهام الظروف المناخية في فصل الشتاء في زيادة حدة التلوث.وعدم ملائمة مواقع المكبات بالنسبة لمواقع السكان وإن المحافظة هي إحدى ضحايا التلوث بشتى أشكاله.
الوضع البيئي في محافظة جنين